Integrase strand-transfer inhibitors for treatment of early HIV infection: A case series. Issue 35 (August 2019) - Teira, Ramón; Gutierrez, Mar; Galindo, Pepa; Martínez, Elisa; Muñoz, Pepa; de la Fuente, Belén; Téllez, Francisco; Montero, Marta
Abstract : Abstract: This study evaluated whether the interval from the first clinic visit until the start of antiretroviral treatment (ART) was correlated with common parameters of immunological recovery among patients with early HIV infection (EHI). We reviewed the medical records of patients with EHI who started ART using integrase strand-transfer inhibitors (ISTIs) within the first 6 months after diagnosis. Simple linear regression analyses were performed to determine whether the interval from the first visit to the start of ART was correlated with 1-year changes in CD4+ cell count, CD8+ cell count, CD4+ percentage, and CD4+/CD8+ ratio. Fifty-three patients with probable or definite EHI started ART using ISTIs between April 2014 and August 2016. Forty-nine patients completed 1 year of follow-up, including 48 men. The routes of HIV transmission were 1 case of needle sharing, 5 cases of heterosexual activity, and 43 cases of men who had sex with men. None of the immunological recovery parameters were correlated with time to the start of ART (CD4+ cell count: R = .12, P = .42; CD8+ cell count: R = .107, P = .5; CD4+ percentage: R = .14, P = .34; CD4+/CD8+ ratio: R = .23, P = .14). Furthermore, subgroup sensitivity analyses failed to detect significant correlations based on definite or probable diagnoses, treatment using elvitegravir or dolutegravir, or the time from HIV diagnosis to ART initiation. This series of EHI cases indicate that using ART with ISTI-based regimens is efficacious and well-tolerated. However, earlier initiation of treatment was not significantly correlated with common parameters of immunological recovery.